2019
DOI: 10.1063/1.5126931
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion of Cu2O studied by quasi-harmonic approximation and cubic force-constant method

Abstract: Cubic cuprous oxide, Cu 2 O, is characterized by a peculiar structural response to temperature: it shows a relatively large negative thermal expansion below 250 K, then followed by a positive thermal expansion at higher temperatures. The two branches of its thermal expansion (negative and positive) are almost perfectly symmetric at low temperatures, with the minimum of its lattice parameter at about 250 K and with the lattice parameter at 500 K almost coinciding with that at 0 K. We perform lattice-dynamical q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
4
9
0
Order By: Relevance
“…5(a) and 5(c) at different temperatures. These Grüneisen parameters are in good agreement with prior QH calculations and experimental results [59]. The plots are color-coded, so the Grüneisen parameters for each mode correspond to the same color mode in the dispersions in Figs.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…5(a) and 5(c) at different temperatures. These Grüneisen parameters are in good agreement with prior QH calculations and experimental results [59]. The plots are color-coded, so the Grüneisen parameters for each mode correspond to the same color mode in the dispersions in Figs.…”
Section: Resultssupporting
confidence: 84%
“…Authors of previous studies of cuprite showed the success of QH theory for predicting thermal expansion [59,[61][62][63][64], and some studies included results on phonon dynamics [61,62,65]. We find similar success with QH theory for thermal expansion and with AH theory.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…[35,36] For a3 dm etal such as Cu, the use of hybrid DFT over GGA or GGA + U is expected to increase the accuracy of the predictions. [37][38][39][40][41][42][43] All-electron, Gaussian-type triple-z-valence + polarization (TZVP) and split-valence + polarization (SVP) basis sets based on Karlsruhe def2 basis sets were used within the crystal structure predictions (a list with of all used basis sets is provided as SI). [44] Cu I ions are expected to show weak "cuprophilic" d 10 -d 10 interactions, [45][46][47][48] which were taken into account in the USPEX search using Grimme's D3 dispersion correction with zero-damping (ZD).…”
Section: Computationaldetailsmentioning
confidence: 99%
“…While calculations based on the density functional theory (DFT) have proved reliable in the prediction of many static properties of materials in the last decades, the effective inclusion of thermal effects still represents a challenge to state-of-the-art DFT methodologies, particularly so when one needs to go beyond the usual harmonic approximation in the description of the lattice dynamics. For instance, this is the case when (i) cubic interatomic force constants are needed to compute phonon lifetimes and the thermal lattice conductivity and (ii) the free energy dependence on volume and strain is needed to determine thermal expansion and thermoelasticity. While the former class of physical properties above requires the explicit evaluation of anharmonic terms of the nuclear potential, the latter has often been tackled within the so-called quasi-harmonic approximation (QHA), as long as inorganic solids were considered. …”
mentioning
confidence: 99%